Dramaturgies on (about) oblivion. Aesthetic and ideological innovations in 1960’s Peruvian dramatic writing - Barraza Eléspuru, Ernesto (2023)
In the 1960s, a generation of dramatic authors emerged in Peru whose work displayed the socially marginalized character front and center for the first time in the local scene. The incorporation of the marginal universe led to the inclusion of new characters, spaces, problems, and, above all, new points of view that distanced themselves from the conventions that the Peruvian public and  critics were accustomed to. This shift meant that authors such as Hernando Cortés, Juan Rivera, Víctor Zavala, Sara Joffré, César Vega and Grégor Díaz developed a dramaturgy where important formal, aesthetic and ideological innovations stood out. This paper provides an analysis of dramatic pieces by the aforementioned authors—mainly those of Díaz, whom we consider most representative of the group—in order to identify their influences and compare and contrast their dramaturgies.